2003
DOI: 10.1111/j.1600-0765.2004.00696.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sub‐antimicrobial dose doxycycline therapy on crevicular fluid MMP‐8, and gingival tissue MMP‐9, TIMP‐1 and IL‐6 levels in chronic periodontitis

Abstract: Adjunctive SDD therapy can improve the clinical parameters and this clinical improvement is reflected by controlled level of MMP-8 in chronic adult periodontitis after the therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
80
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 25 publications
11
80
1
Order By: Relevance
“…Third, though the concentration of TIMP-1 expressed was not enough to show the difference of MMP expression between the groups, the target cells to TIMP-1 in the inflammatory areas are increased in periodontitis group compared to control group which might enhance the chance of activation 12,21) . Fourth, the activity of MMPs is tightly regulated at sev-eral levels including gene expression, secretion of pro-enzymes that require activation and inhibition by TIMPs [40][41][42][43] . Death et al 44) found that high glucose may regulate MMP gene expression via its effects on gene transcription or growth factors through the increased activation of its own response elements.…”
Section: Discussionmentioning
confidence: 99%
“…Third, though the concentration of TIMP-1 expressed was not enough to show the difference of MMP expression between the groups, the target cells to TIMP-1 in the inflammatory areas are increased in periodontitis group compared to control group which might enhance the chance of activation 12,21) . Fourth, the activity of MMPs is tightly regulated at sev-eral levels including gene expression, secretion of pro-enzymes that require activation and inhibition by TIMPs [40][41][42][43] . Death et al 44) found that high glucose may regulate MMP gene expression via its effects on gene transcription or growth factors through the increased activation of its own response elements.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have evaluated the effectiveness of low-doses doxycycline (LDD) therapy as an adjunct to nonsurgical periodontal therapy in which LDD was prescribed from 2 weeks to 12 months [24][25][26][27][28][29][30][31][32][33]. These long-term, double-blind, placebo-controlled clinical studies have reported that a combined regimen of LDD and nonsurgical periodontal therapy resulted in signifi cant improvement in clinical periodontal parameters in combination with a signifi cant decrease in collagenase activity when compared to nonsurgical periodontal therapy alone [26,29,30,32]. It was also indicated that long-term usage of LDD is not associated with the development of TC resistant microorganisms or exert any detrimental effect on the periodontal microfl ora [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…SDD has high affinity to bone and soft tissues, thus, its accumulation in the periodontium would further enhance its curative effect [15]. Chio et al [8] reported similar results after administration of SDD that was associated with significant decrease in MMP-8 level in their patients' GCF.…”
Section: Discussionmentioning
confidence: 87%
“…It is used in low dose formulation that has no antimicrobial activity, and it acts as a host modulatory agent [7]. This non-antimicrobial action include the inhibition of tissue destruction by direct inhibition of Matrix Metalloproteinases (MMPs) [8] in the gingival tissues, inhibition of bone resorption by regulation of MMPs released by osteoclasts [9] and inhibition of MMPs precursors activation [10]. The host modulatory effects of sub-antimicrobial dose doxycycline (SDD) have been stated by several clinical studies [11][12][13].…”
Section: Introductionmentioning
confidence: 99%